INCREASING CRIMINAL PENALTIES FOR PERPETRATORS WHO FORCE SEXUAL RELATIONS WITH CHILDREN (Study of Decision No. 253/Pid.Sus/2025/PN.Kis) - Diya Duta Ramanda; Nurhilmiyah Nurhilmiyah (Inspiring Law Journal, 2025)
This study discusses the aggravation of criminal penalties against perpetrators who force children to engage in sexual intercourse, with a focus on Decision Number 253/Pid.Sus/2025/PN.Kis. Cases of sexual violence against children in Indonesia continue to increase and have serious impacts on children’s futures, both physically and psychologically. These crimes become even more concerning when committed by individuals closest to the victim, such as a stepfather, who should provide protection and a sense of security to the child. This research aims to analyze the legal regulations regarding the aggravation of punishment for perpetrators of forced sexual intercourse against children, the forms of coercion committed by the perpetrator, and the judge’s considerations in rendering the decision in Case Number 253/Pid.Sus/2025/PN.Kis.The research method used is normative legal research with statutory and case approaches. The data sources consist of primary, secondary, and tertiary legal materials analyzed qualitatively. The results of the study show that the aggravation of criminal sanctions against perpetrators of sexual violence against children is regulated under Law Number 17 of 2016 concerning Child Protection, including the possibility of imposing additional measures in the form of chemical castration. In the case examined, the judge sentenced the defendant to 12 years of imprisonment and a fine but did not impose additional measures such as chemical castration, despite the repeated acts and threats committed against the victim. Therefore, stricter and more proportional sanctions are necessary to create a deterrent effect and ensure the protection of children as victims of sexual violence.